Uncommon BRAF Mutations Associated with Durable Response to Immunotherapy in Patients with Metastatic Melanoma - Brenen P. Swofford; Jade Homsi (Case Reports in Oncological Medicine)
Melanoma is a disease process which has been increasing in incidence over the past three decades and metastatic melanoma carries a poor prognosis. Through genetic studies of this disease, it has been determined that the BRAF V600 mutation plays a major role in the pathophysiology of the disease and this has led to the utilization of targeted therapy (BRAF and MEK inhibitors) in its treatment. Other BRAF mutations (non-V600 mutations) are rare in melanoma and targeted therapy is not indicated for patients with these mutations due to reduced response rates. An emerging option for metastatic melanoma with uncommon BRAF mutations is immunotherapy using checkpoint inhibitors such as PD-1 inhibitors or CTLA-4 inhibitors. Currently, it is unknown how patients with BRAF non-V600 mutations respond to immunotherapy. This report will examine the effect of immunotherapy on two distinct metastatic melanoma patients, each with uncommon BRAF mutations, occurring outside the V600 locus (E586K and G469E). These patients were noted to have a durable, complete response when treated with immunotherapy and continue to exhibit a response 9 and 15 months after discontinuing therapy. Further research and clinical trials are needed to study patients with uncommon BRAF mutations and the potential therapeutic benefit of immunotherapy.